2023
DOI: 10.3389/fcimb.2023.1149032
|View full text |Cite
|
Sign up to set email alerts
|

Atypical flavobacteria recovered from diseased fish in the Western United States

Abstract: Flavobacterial diseases, caused by bacteria in the order Flavobacteriales, are responsible for devastating losses in farmed and wild fish populations worldwide. The genera Flavobacterium (Family Flavobacteriaceae) and Chryseobacterium (Weeksellaceae) encompass the most well-known agents of fish disease in the order, but the full extent of piscine-pathogenic species within these diverse groups is unresolved, and likely underappreciated. To identify emerging agents of flavobacterial disease in US aquaculture, 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 106 publications
0
1
0
Order By: Relevance
“…Histological analysis of the five killed rainbow trout revealed that the spleen presented lymphoid hyperplasia in three and two samples obtained from bath (Figure 2) and intraperitoneal injection challenged fish, respectively. The score of these five fish was two Heckman et al, 2023;Nhinh et al, 2023;Zamora, Fernandez-Garayzábla, et al, 2012;.…”
Section: Challenge Assaymentioning
confidence: 99%
“…Histological analysis of the five killed rainbow trout revealed that the spleen presented lymphoid hyperplasia in three and two samples obtained from bath (Figure 2) and intraperitoneal injection challenged fish, respectively. The score of these five fish was two Heckman et al, 2023;Nhinh et al, 2023;Zamora, Fernandez-Garayzábla, et al, 2012;.…”
Section: Challenge Assaymentioning
confidence: 99%
“…35 (14). W ostatnich latach opisano także kilka nowych gatunków Flavobacterium, jak: F. plurextorum, F. tructae, F. collinsii, F. oncorhynchi i F. piscis, które zostały wyizolowane od narybku pstrąga tęczowego, mającego objawy kliniczne podobne do tych występujących przy zakażeniu F. psychrophilum (16). By móc wykorzystać metodę MALDI-TOF MS do odróżniania tych bakterii, Perez-Sancho i wsp.…”
unclassified